2021
DOI: 10.14814/phy2.14937
|View full text |Cite
|
Sign up to set email alerts
|

Early triggers of moderately high‐fat diet‐induced kidney damage

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 72 publications
0
4
1
1
Order By: Relevance
“…Regarding the effect of a high-fat diet on the kidney, Sánchez-Navarro et al showed that a high-fat diet does not have an effect on the kidney weight; however, the ratio of kidney/body weight (KW/BW) was reduced . However, our study did not show differences in the kidney weight.…”
Section: Resultscontrasting
confidence: 78%
“…Regarding the effect of a high-fat diet on the kidney, Sánchez-Navarro et al showed that a high-fat diet does not have an effect on the kidney weight; however, the ratio of kidney/body weight (KW/BW) was reduced . However, our study did not show differences in the kidney weight.…”
Section: Resultscontrasting
confidence: 78%
“…Like in patients with chronic kidney disease, lipid droplets have been observed in the kidneys of HFD rats and mice (Deji et al, 2009;Jiang et al, 2005;Sun et al, 2020;van der Heijden et al, 2015) and have been associated with dysfunctional cellular systems including oxidative stress, renal inflammation, ER-stress, disruption of mitochondrial dynamics, and impaired autophagylysosomal pathway in the cells of the kidneys (Cai et al, 2024;Ha et al, 2022;Kuwahara et al, 2016;C. Li et al, 2016;Lu et al, 2003;Rangel Silvares et al, 2019;Ruggiero et al, 2011;Sánchez-Navarro et al, 2021;Sun et al, 2020;Szeto et al, 2016;van der Heijden et al, 2015). Altogether, these indicate the involvement of both local and systemic changes (Deji et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Podocytes from patients with chronic kidney disease contain lipid droplets that store excess fat (Herman-Edelstein et al, 2014; Kimmelstiel and Wilson, 1936), these cause lipotoxicity by disrupting the mitochondria, as well as endocytosis (Lubojemska et al, 2021), a process crucial to the kidney filtration structure (Wang et al, 2021). Studies in rats and mice on a HFD have repeatedly shown that the animals suffer from obesity, diabetes (altered insulin homeostasis), and kidney injury marked by functional (albuminuria; blood accumulation of BUN and creatinine; increased urinary biomarkers of kidney damage) and structural (glomerulopathy with glomerular hypertrophy and focal segmental glomerulosclerosis; fibrosis) deficiencies (Altunkaynak et al, 2008; Ha et al, 2022; Jiang et al, 2005; Kuwahara et al, 2016; Lu et al, 2003; Rangel Silvares et al, 2019; Ruggiero et al, 2011; Sánchez-Navarro et al, 2021; Sun et al, 2020; Szeto et al, 2016; van der Heijden et al, 2015). Like in patients with chronic kidney disease, lipid droplets have been observed in the kidneys of HFD rats and mice (Deji et al, 2009; Jiang et al, 2005; Sun et al, 2020; van der Heijden et al, 2015) and have been associated with dysfunctional cellular systems including oxidative stress, renal inflammation, ER-stress, disruption of mitochondrial dynamics, and impaired autophagy-lysosomal pathway in the cells of the kidneys (Cai et al, 2024; Ha et al, 2022; Kuwahara et al, 2016; C. Li et al, 2016; Lu et al, 2003; Rangel Silvares et al, 2019; Ruggiero et al, 2011; Sánchez-Navarro et al, 2021; Sun et al, 2020; Szeto et al, 2016; van der Heijden et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The unmetabolised FA pool is converted into triglycerides and stored in epithelial cells in the form of lipid droplets (Tang et al, 2016). These perturbations in energetic metabolism induce oxidative stress, which requires the activation of stress-preventing mechanisms, such as reactive oxygen species (ROS) scavengers and molecular chaperones, to preserve cell function (Sun et al, 2020;Sánchez-Navarro et al, 2021). Moreover, prolonged stress related to increased fat intake, such as ectopic lipid accumulation and lipid peroxide production, may lead to the induction of an inflammatory response and activation of pathways involved in increased extracellular matrix deposition (Yang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%